Relevance of lipid metabolism for brown fat visualization and quantification. Issue 3 (June 2016) - Schilperoort, Maaike; Hoeke, Geerte; Kooijman, Sander; Rensen, Patrick C.N.
Abstract : Purpose of review: Brown adipose tissue (BAT) is an emerging target to combat cardiometabolic disorders as it can take up substantial amounts of glucose and lipids from the circulation for heat production. This review focuses on new concepts in BAT physiology and discusses the need for new techniques to determine BAT activity in humans. Recent findings: Mouse studies showed that BAT activation selectively increases oxidation of lipids over glucose, by recruiting fatty acids from intracellular triglycerides. To replenish these intracellular lipid stores, brown adipocytes take up both glucose and triglyceride-derived fatty acids, resulting in attenuation of dyslipidaemia, insulin resistance and atherosclerosis. Clinical studies identified the involvement of the β3-adrenergic receptor in BAT activation and demonstrated that human BAT activation also selectively increases lipid oxidation. Notably, insulin resistance during ageing or weight gain reduces the capacity of BAT to internalize glucose, without reducing fatty acid uptake or oxidative metabolism. Summary: Preclinical studies established BAT as an important target to combat cardiometabolic disorders and elucidated underlying mechanisms whereas clinical studies identified therapeutic handles. Development of novel lipid-based PET-CT tracers and identification of translational biomarkers of BAT activity are required as alternatives to [ 18 F]fluorodeoxyglucose PET-CT to accelerate clinical development of BAT-activating therapeutic strategies.